Numerical Elastoplastic Analysis of Trabeculae in Lumbar Vertebral Body - MAKNICKAS, Algirdas; ALEKNA, Vidmantas; ARDATOV, Oleg; KIZILOVA, Natalya; TAMULAITIENĖ, Marija; KAČIANAUSKAS, Rimantas (Engineering Transactions, 2017)
This paper presents a numerical modelling of lumbar vertebrae L1 by employing the finite element method. The three-dimensional model of vertebral body is derived by processing CT data and DICOM format files. The model includes cortical shell, trabecular bone and posterior elements. The formation of trabecular structure was performed by script-controlled ellipsoidal cut-outs. In order to define the nonlinear relationship between the stress and the strain, the Ramberg-Osgood equation was applied. Therefore, the von Mises stress was assumed to characterise the stressed state of bone tissue due to 1 and 7 MPa compression load. According to specific difficulties for “in vitro” and “in vivo” investigation methods, this “in silico” technique may provide new insight for further understanding of the trabecular bone behaviour in terms of plastic deformation.